(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Diabetes of the bearded women was first described by Achard and Theirs in 1921 and since then insulin resistance and hyperinsulinemia in women with polycystic ovary syndrome (PCOS) remains one of the commonest metabolic problems. Insulin resistance and type II diabetes mellitus occurs in 70% of women with PCOS. The mechanism of insulin resistance has not been well established and inconsistent study results have complicated treatment modalities and management of insulin resistance and PCOS in general. There is evidence that 80% of women with PCOS are deficient in Vitamin D and this could be the missing link between Vitamin D and insulin resistance. Objective: To determine the correlation of Vitamin D, AMH and glycemic status in infertile PCOS, infertile non PCOS patients and fertile non PCOS attending Mediheal Fertility Center in Western Kenya as there is dearth of such studies within Kenyan population. Methods: A case control design with 20 patients per group for infertile PCOS, infertile non PCOS and fertile non PCOS which served as normal controls. Quantification of HbA1c was done at AMPATH reference laboratories using fluorescence immunoassay while Vitamin D and AMH was done at MTRH laboratories using ECLIA Roche. Data was analyzed using Statistical Package for Social Sciences (SPSS) version 25. Results: The mean HbA1c and median serum AMH in infertile PCOS, infertile non PCOS and infertile non PCOS were 6.1±0.4 and 7.5(6.2, 11.1), 5.5±0.3, and (1.2, 4.4), 5.6±0.3 and 2.0(1.7, 2.3) respectively. The study revealed statistically significant increase in HbA1c and serum AMH in infertile PCOS as compared to infertile non PCOS and fertile non PCOS (F=15.7, p<0.001 and F=46.7, p<0.001) respectively. In addition, Vitamin D was significantly deficient among infertile PCOS versus infertile non PCOS and fertile non PCOS (F=41.8, p<0.001). Conclusion: Infertile patients with PCOS have deficiency in Vitamin D and increase in HbA1c and AMH hence there might be a link of Vit D and AMH in pathophysiology of insulin resistance among PCOS patient